(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research investigates into the vibrant urban food-scape of Madurai, where roadside eateries serve not just as food outlets but also as reflections of the socio-economic conditions prevalent in the area. These eateries attract a broad spectrum of patrons, characterized by a significant female majority and a predominantly young, educated demographic from various religious backgrounds. The study highlights the key influences on consumer choices, such as affordability, convenience, and cultural preferences, which are pivotal in understanding the dynamics of street food consumption in a culturally rich and economically diverse city like Madurai. The findings offer insights into how these eateries cater to and are shaped by the urban population, providing stakeholders valuable data to tailor their services effectively to meet the evolving tastes and preferences of their consumers.